Atypical Cogan syndrome: a case report - K. El Bouhmadi; A. Allaoui; M. El Khattab; M. Youbi; S. Anajar; M. Essaadi; K. Snoussi; A. Hajjij (Journal of Medical Case Reports, 2024)
Abstract Background Cogan syndrome is a rare autoimmune systemic vasculitis presenting with interstitial keratitis and audiovestibular symptoms. The atypical form, characterized by more extensive ocular lesions with audiovestibular symptoms appearing with a longer delay and more frequent systemic features, is usually underdiagnosed, delaying treatment. Case presentation We report the case of a 30-year-old Mediterranean female who presented recurrent left red and painful eye. The evolution in flare-ups during 3 years, associated with a nonspecific biological inflammatory response, motivated ocular biopsies demonstrating diffuse inflammatory changes from the cornea to the sclera. Since Morocco is an endemic region for tuberculosis, the laboratory tests were expanded to identify the latent forms based on the tuberculin skin test and QuantiFERON TB Gold in tube assay, both positive for Mycobacterium tuberculosis infection. Thus, antibacillary chemotherapy was started for 6 months, with reappearance of the symptoms at the end of treatment. Three years later, the patient presented isolated and fluctuating audiovestibular Ménière-like symptoms, with progressive sensorineural hearing loss. The nonstabilization under usual medical treatment along with her diffuse inflammatory ocular lesions led to the diagnosis of atypical Cogan syndrome. The patient received long-term corticosteroid with notable improvement. Conclusion Cogan syndrome is a rare autoimmune disease that should be considered when faced with ocular and audiovestibular manifestations, even in its atypical form, to provide early and adequate treatment, which is the main prognosis factor in the control of irreversible lesions. Thus, interdisciplinary collaboration is fundamental along with screening for other infectious and systemic disorders that should include tuberculosis.